Exploring the Influence of Translocation Factors on International Students’ Well-being - Movahed, Mahtab Sadri (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2020)
Un-dubiously, the pivot of human performance has been established based on a healthy lifestyle and general well- being. Plenty of studies have argued the involvement of different factors that can manipulate a healthy lifestyle. Between all these factors, translocation stressors have been singled out, addressed in depth among immigrants, refugees, asylum seekers, nomadic native people, newly translocated individuals and migrating ethnic groups. On the contrary, the impact of this phenomenon has not been exhausted in-depth, on the most vulnerable nomadic population, “international students” as they temporarily dwell overseas. In this particular study, a healthy lifestyle was measured by diet, sleep and lack of stress. We presumed that stress due to translocation, specifically acculturative stressors can tamper with sleep patterns and a healthy lifestyle of international students, who were studying master of tourism management at Eastern Mediterranean University, located in North Cyprus. In this study, both genders, different ages (mean of 25), different communities such as: Africans (Nigerians, Moroccans), Middle Easterners (Iranians), Asians (Tajiks, Jordanians, Pakistanis, Turkmen, and plantains) and Europe (Russians) were taken into equation. In order to attain the purpose of this study, data compiled via an inductive approach (self-administered interview). Participants approached through email or their personal contact numbers to attend in either one o’ one or group interviewees in order to establish a transparent picture on the translocation stressors which could create emotional stress for the subject in the novel environment. In conclusion, among all the introduced stressors, financial impediments and language barrier [academic/host community] were highlighted as chief stressors, which reinforced the results of previous studies over physiological and psychological impact on the sleep cycle, nutritional behavior and further down the road, well-being of international students. Keywords: International students, Dietary patterns, Sleep cycle, Healthy life-style, Acculturative stress, Translocation stress, Emotional regulation strategy

ÖZ: Şüpesizce insan performansı sağlıklı yaşam tarzı ve genel iyilik hali ile bağlantılıdır. Birçok araştırma diğer faktörlerin de sağlıklı bir yaşam tarzını etkilediğini savunmuştur. Bu faktörler arasında translokasyon stresi göçmenler, mülteciler, sığınmacılar, göçebe yerliler, yakın zamanda yer değişen insanlar ve göç eden etnik gruplar üzerinde detaylı olarak incelenmiştir. Ancak, bu olgunun etkileri geçici olarak yurtdışında okuyan “uluslararası öğrenciler” üzerinden detaylı bir şekilde incelenmemiştir. Bu araştırmada sağlıklı yaşam tarzı beslenme biçmi, uyku ve stressizlik üzerinden ölçülmüştür. Translokasyon stresinin (ve özellikle akültüratif stress faktörlerinin) Kuzey Kıbrıs’da bulunan Doğu Akdeniz Üniversitesi’nde Turizm İşletmeciliği okuyan uluslararası öğrencilerin uyku düzenini ve sağlıklı yaşam tarzını bozabileci varsayılmıştır. Bu araştırmaya her iki cinsiyetten, yaş ortalaması 25 olan Afrikalı (Nijeryalı, Faslı), Orta Doğulu (İranlı), Asyalı (Tacik, Ürdünlü, Pakistanlı, Türkmen) ve Avrupalı (Rus) öğrenciler katılmıştır. Araştırmanın amacına ulaşmabilmesi için tümevarım yaklaşımı altında mülakatlar gerçekleştirilmiştir. Hangi translokasyon stres faktörlerinin yeni çevrelerinde katılımcılara duygusal stres yaratabileciğini şeffaf bir şekilde belirlemek için onlara e-posta veya kişisel telofonları üzerinden ulaşılıp teke tek veya grup halinde mülakatlar gerçekleştirilmiştir. Sonuç olarak, finansal ve [akademik/ev sahibi topluluk] ile olan dil engelleri başlıca stres faktörleri olarak belirlenmiştir. Böylece bu araştırmadan çıkan sonuç uluslararası öğrencilerin fizyolojik ve psikolojik durumlarının uyku düzenlerini, beslenme biçimlerini ve sonraki zamanlardaki sağlık durumlarını nasıl etkileyebileceği üzerine yapılan önceki araştırmaların sonuçlarını desteklemiştir. Anahtar kelimeler: uluslararası öğrenciler, beslenme biçimleri, uyku döngüsü, sağlıklı yaşam tarsi, akültüratif stres, translokasyon stresi, duygusal düzen stratejisi
Master of Science in Tourism Management. Institute of Graduate Studies and Research. Thesis (M.S.) - Eastern Mediterranean University, Faculty of Tourism, 2020. Supervisor: Asst. Prof. Dr. İlkay Yorgancı.
Keywords: Tourism; Tourism--Educational Tourism--Eastern Mediterranean University--Famagusta--Cyprus (Turkish Republic of Northern Cyprus, 1983-); Students--Travel--Foreign study--Tourism--Eastern Mediterranean University; Tourism--Study and teaching (Higher)--Cyprus, North; International Students--Eastern Mediterranean University--Famagusta--Cyprus (Turkish Republic of Northern Cyprus, 1983-); Hospitality industry--Study and teaching (Higher)--Cyprus, North; International students; Dietary patterns; Sleep cycle; Healthy life-style; Acculturative stress; Translocation stress; Emotional regulation strategy